SUMBER DAYA MANUSIA YANG TANGGUH DALAM MEMBANGUN KOPERASI (Sebuah Tinjauan Praktis) - Jamil, TM (Universitas Muhammadiyah Aceh, 2010)
Unability of cooperative to be the solution of the mainstay institution of SMEs empowerment was not because of the wrong basic concept of cooperative institution but it was because of development approach which is directly influenced by political policy and economy of the world. Globalization is one of the factor which should encourage cooperative development (it is a challenge so that SMEs group to be united in the frame of enhancing the scale of business and efficiency), nevertheless its tendency becomes a constraint to the sustainability of cooperative development. Solution which is needed to empower cooperative is a strong and real commitment by revitalizing cooperative activities and enforcement of financing. Alternative in purifying cooperative institution could be done by way of: 1) Improving and completing cooperative law (accelerate the ratification of cooperative bill); 2) Giving extention, training and education to cooperative board of directors, managers and method so as they could really know and understand about cooperative completely and genuinely: 3) Appropriate, directed, planned and sustainable socialization/ promotion through media; 4) Preparing appropriate standard and method of cooperative subject to support cooperative cadres forming on the basic, medium and high education; and 5) Giving most of promotion and responsibility on cooperative development to cooperative movement itself. DAFTAR PUSTAKA Anonimus, (2006). Kumpulan hasil-hasil Workshop Pemberdayaan Koperasi dan UMKM. Deputi Bidang Pengkajian Sumberdaya Koperasi dan UMKM (laporan sementara belum diterbitkan). Surya Dharma Ali, (2007). Komitmen Pemberdayaan UMKM dan Koperasi. Disampaikan pada Seminar Prospek Usaha Kecil dan `Menengah, Lembaga Usaha Pengembangan Masyarakat Jakarta. Nasution Muslimin, (2001). Koperasi, Konsepsi Pemikiran dan Peluang Pembangunan Masa Depan Bangsa. ————– , (1996). Membangun Koperasi Sebagai Wahana Efektif Untuk Memberdayakan Perekonomian Rakyat. Badan Perencanaan Pembangunan Nasional Jakarta. Ibnu Soedjono. Et.al, (1996). koperasi Di Tengah Arus Liberalisasi Ekonomi. FORMASI, Jakarta.